2019
DOI: 10.1111/ajt.15228
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant sequential hypo- and normothermic machine perfusion of suboptimal livers donated after circulatory death using a hemoglobin-based oxygen carrier perfusion solution

Abstract: Ex situ dual hypothermic oxygenated machine perfusion (DHOPE) and normothermic machine perfusion (NMP) of donor livers may have a complementary effect when applied sequentially. While DHOPE resuscitates the mitochondria and increases hepatic adenosine triphosphate (ATP) content, NMP enables hepatobiliary viability assessment prior to transplantation. In contrast to DHOPE, NMP requires a perfusion solution with an oxygen carrier, for which red blood cells (RBC) have been used in most series. RBC, however, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
168
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(183 citation statements)
references
References 33 publications
14
168
0
1
Order By: Relevance
“…Due to the lack of NADH‐dependent enzyme (methemoglobin reductase) in HBOC, the possibility of Met‐Hb production is a disadvantage associated with HBOC use and the gradual rise in Met_Hb level has been previously reported . Our experiments also revealed a slight increase in the Met‐Hb during rewarming and more extreme during reperfusion.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Due to the lack of NADH‐dependent enzyme (methemoglobin reductase) in HBOC, the possibility of Met‐Hb production is a disadvantage associated with HBOC use and the gradual rise in Met_Hb level has been previously reported . Our experiments also revealed a slight increase in the Met‐Hb during rewarming and more extreme during reperfusion.…”
Section: Discussionsupporting
confidence: 64%
“…The use of HBOC in 2 discarded human liver studies reported the feasibility and safety of applying HBOC‐based perfusion media during normothermic machine perfusion (NMP) as an alternative to RBCs . A recent study by de Vries et al described the use of HBOC in a pretransplant combined dual oxygenate hypothermic machine perfusion (D‐HOPE) with controlled oxygenated rewarming (COR) to NMP in initially declined human liver grafts . The study presented promising results for further future use of HBOCs in clinical studies with the outcome of 100% patient survival in the first 3 months post‐transplant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PRBC. However, the amount of HBOC reaching the recipient circulation in a clinical setting would be negligible, because the perfusion solution would be washed out prior to transplantation 26,27,38,39. Histology reveals glomerular tufts irregularly engorged with accumulated luminal red blood cells (black arrows), loss of the epithelial brush border, frequent cytoplasmic vacuolations (blue arrows), and rupture of some tubules with interstitial edema (red arrows).…”
mentioning
confidence: 99%